Testing of diagnostic test-systems for detection of antibodies to foot-and-mouth disease virus structural proteins with enzyme-linked immunosorbent assay for their serotype specificity - N. N. Lugovskaya; E. A. Silanteva; T. V. Okovytaya; A. A. Kharitonova; Y. M. Gochmuradov; E. A. Razgulyaeva; O. O. Budina; E. A. Yasneva (Ветеринария сегодня)
A total of 138 serum samples from pigs and cattle vaccinated against foot-and-mouth disease virus (FMDV) of one or two serotypes or infected with FMDV were used for testing of 24 enzyme-linked immunosorbent assay (ELISA) diagnostic tests-systems for detection of antibodies against FMDV structural proteins produced by 6 manufacturers (Federal Centre for Animal Health, Prionics, IZSLER, Innovative Diagnostics, BIONOTE and MEDIAN Diagnostics) for their serotype-specificity. All used test-systems detected apparent serotype-specific activity (homologous reaction) as well as cross-reacting virus-specific antibodies that was accounted for some reasons related to conservative epitopes in amino acid sequence of FMDV virion capsid VP1–VP3 polypeptides, accessibility of internal conservative epitopes of VP4 polypeptide for the animal’s immune system during virus replication or vaccine antigen (virus) destruction in the animal’s body in the process of immunity development, as well as the pilot anti-FMD vaccine composition, etc. Nevertheless, the analysis of a large data set (about 3,500 tests) showed that the homologous serotype-specific reaction in general was significantly higher and predominant, the proportion of virus-specific non-protective antibodies, including cross-reacting ones, was not significant and did not distort the results of ELISA tests of anti-FMD vaccine for its immunogenicity. Inconclusive test results require confirmation with other serological tests. Complex tests for FMDV using different diagnostic methods such as ELISA with standard and reference test-systems and/or virus neutralization test in cell culture are to be considered as the best option.